Funcionais paramétricos elípticos em variedades riemannianas - Melo, Marcelo Ferreira de (2009)
It is stated that critical points of a parametric elliptic functional in a Riemannian manifold are hypersurfaces with prescrebed anisotropic mean curvature. We prove that the anisotropic Gauss map of surfaces immersed in Euclidean space with constant anisotropic mean curvature is a harmonic map. In the case of rotatioally invariat functionals in some homogeneous three-dimensional ambients, we present a abridged version of a existence result for constant anisotropic mean curvature surfaces as cylinders, spheres, tori and annuli corresponding to the anisotropic analogs of onduloids and nodoids. In the Euclidean case M¯ = R3, examples of stable critical points are provided by theWulff shapes associated to functional F. Paralleling the case of constant curvature mean spheres, a characterization of Wulff shapes is provided, which answers affirmatively a question posed by M. Koiso and B. Parmer in [13].